EVALUASI KEBIJAKAN PROGRAM PERUMAHAN BERSUBSIDI DI KOTA TANJUNGPINANG: ANALISIS BERDASARKAN LAPORAN PENYELENGGARAAN PEMERINTAHAN DAERAH (LPPD) TAHUN 2023: - , Nia Angelina Ramadhani; Suryana Br Manurung; Erlin Christinia Halawa (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
The provision of decent and affordable housing is one of the strategic priorities pursued by the Tanjungpinang City Government to improve the welfare of its citizens. Despite the implementation of various subsidized housing programs, significant challenges remain, particularly related to limited budgets, minimal developer involvement, and inadequate provision of public facilities and utilities (PSU). This has resulted in several program targets not being optimally achieved, as reflected in the 2023 Regional Government Performance Report (LPPD). This study aims to evaluate the policies of subsidized housing programs in Tanjungpinang using a document analysis method. The primary data used is from the 2023 LPPD and related performance reports. This approach was chosen to understand to what extent the designed policies can be effectively implemented in the field, and to identify obstacles that hinder the achievement of the program. The research results are expected to provide insights and recommendations for more effective policies to address existing constraints and increase public access to decent and affordable housing. The discussion of the research results will focus on analyzing program achievements, challenges faced, and potential improvements for future subsidized housing programs.